First Order Kinetics of Biodiesel Synthesis Using Used Frying Oil through Transesterification Reaction - Agus Haryanto; Amieria Citra Gita; Tri Wahyu Saputra; Mareli Telaumbanua (Graduate Program of Syiah Kuala University, 2020)
This research aims to study the first-order kinetics of biodiesel production from used frying oil (UFO) through transesterification with methanol. Used frying oil was collected from fried peddlers around the campus of the University of Lampung. Technical grade methanol and NaOH catalyst were purchased from a local chemical supplier. The experiment was carried out with 100 ml of UFO at various combinations of oil to methanol molar ratio (1:4, 1:5, and 1:6), reaction temperatures(30 to 55oC, the ramping temperature of 5o C), and reaction time of 0.25 to 10 minutes. First-order kinetic was employed using 126 data pairs (87.5%). The acquired kinetic model was validated using 18 data sets (12.5%) observed at a reaction time of eight min. Results show that biodiesel yield was increased with reaction time, its molar ratio, and temperature. The maximum return of 78.44% was achieved at 55oC and molar ratio of 1:6. The kinetic analysis obtains the reaction rate constant (k) in the range of 0.045 to 0.130. The value of k increases with the reaction temperature and molar ratio. The analysis also reveals the average activation energy (Ea) of the UFO transesterification reaction with methanol and NaOH catalyst to be 21.59 kJ/mol. First-order kinetic is suitable to predict biodiesel yield from UFO because of low %RMSE (3.39%) and high R2 (0.8454